The Moderating Effect of Cultural Intelligence on the Relationship Between Emotional Intelligence and Job Satisfaction - Bal, Yasemin; Kökalan, Özgür (Frontiers in Psychology, 2022)
It is seen that employees with high emotional intelligence (EI) generally have low level of job stress; they can also integrate better with their jobs and provide a high level of job satisfaction (JS). This study aims to investigate the moderating effect of the cultural intelligence (CI) level of academicians on the relationship between their EI and JS. The data were collected from 470 academicians working in Turkish universities. The sample consists of 3 sub-groups: academicians that are Turkish citizens of and completed their entire education in Turkey, academicians that are Turkish citizens and received a part of their education abroad, and academicians that are not citizens of Turkey and completed their education outside of Turkey. According to the research results, it was found that there is a significant positive relationship between the EI level of the academicians and their JS. The research also determined that CI had a moderating effect on the positive relationship between EI and JS. The CI level of the academicians strengthens the positive relationship between their EI and JS.